Auxin Directly Upregulates GhRAC13 Expression to Promote the Onset of Secondary Cell Wall Deposition in Cotton Fibers - Zhang, Mi; Cao, Huizhen; Xi, Jing; Zeng, Jianyan; Huang, Juan; Li, Baoxia; Song, Shuiqing; Zhao, Juan; Pei, Yan (Frontiers in Plant Science, 2020)
Cotton fibers are single cells that show a relatively independent developmental process of cell differentiation, elongation, and secondary wall deposition. Auxin promotes fiber cell protrusion from the surface of the ovule. However, the role of auxin at other stages of cotton fiber development remains largely unknown. To gain a deeper insight into this aspect, we measured indoleacetic acid (IAA) content in developing fibers. Results showed an increase in IAA content at the transition stage from elongation to secondary cell wall deposition. Subsequently, we investigated the differences between two transgenic cottons that show upregulated and downregulated fiber auxin levels, respectively. In planta analysis revealed that, in addition to promoting cell elongation, auxin regulated the time of initiation of reactive oxygen species (ROS) production and secondary wall deposition in cotton fibers. This was closely correlated with the upregulated expression of GhRAC13, which regulates ROS-triggered cellulose synthesis. We found multiple putative auxin-responsive elements existed within the promoter region of GhRAC13, and IAA could induce proGhRAC13 activity. The dual-luciferase reporter assay further proved the activation of proGhRAC13 by GhARF5, an auxin-signaling activator. Altogether, our results suggest a role of auxin in promoting the onset of secondary growth by directly upregulating GhRAC13 expression in cotton fibers.